Japan Through the Lens of the Tokyo Olympics Open Access. - Holthus, Barbara; Gagné, Isaac; Manzenreiter, Wolfram; Waldenberger, Franz (Milton : Taylor & Francis Group, 2020)
This book situates the 2020 Tokyo Olympics within the social, economic and political challenges facing contemporary Japan.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books